Filicide-suicide: a case report on triple hanging - Parajuli, Sudhir Raman (Journal of Chitwan Medical College, 2021)
Dyadic deaths involve deaths that occur when two or more persons die together or one after another in the same incident. Filicide-suicide is a variant of homicide-suicide which includes the killing of children by a parent. We bring here a rare case of a father with his two children found hanging in a shed with a use of single ligature material, nylon rope. The children were of age three and five years. It happened when wife of the man had run away with another man leaving them behind for 15 days.